Perceptual recall and emotional anchoring: The role of autobiographical memory in shaping attitudes toward maternal food experiences - Tuğcu, Elçin Duygu; İnce Karaçeper, Ecem (Peter Lang Group AG, 2026)
Nutrition is not only fundamental physiological requirement that ensures an individual’s survival but also a critical factor in influencing cognitive and emotional development. Among the most potent stimuli in an individual’s memory are the senses of taste and smell. Tastes encountered unknowingly in daily life do not merely fulfill nutritional requirements. Furthermore, they reflect the emotional resonances of previous experiences. Especially maternal meals are deeply intertwined with childhood recollections, and these flavors shape their food preferences, cultural identity, and emotional responses throughout adulthood (Herz, 1996). The most significant effect of taste memory is explained through autobiographical memory, emotional connections, collective memory, and neuroscientific processes. Although biological predispositions form the foundation of individuals’ dietary habits and preferences, the socio-cultural context and environmental conditions in which the reside play a pivotal role in further modulating these patterns. Empirical findings reveal that infants who are breastfed are more inclined to accept diverse flavors, a tendency attributed to the maternal nutritional intake (Mennela et al., 2001). Early exposure to various tastes contribute to the formation of a flavor map that shapes dietary preferences in later stages of life. In addition, the flavors frequently encountered during childhood contribute to fostering a sense of security and comfort in adulthood (Troisi et al., 2015). In response to emotional conditions such as stress, nostalgia, or loneliness, individuals are inclined to favor familiar flavors as a coping mechanism in their dietary preferences. This phenomenon highlights the intricate interplay between taste memory and emotional bonds, demonstrating its impact on psychological responses.
Keywords: Cognitive development; Emotional development; Taste memory; Olfactory memory; Nutrition